El adjetivo verbal de obligación –nd- y la expresión del agente - Santos Guzmán, Patricia (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
It is mentioned in a great of syntax works that the –nd-obligation adjetive can be completed by a dativ lexem cxpresing the agent that accomplish the verbal action; it is also said that this “agent” can be expressed by ab+ablativ, which is also used in the passive voice. This work will try to show, through examples taken from latin texts, when and why this expressing procedures (dativ and ab+ablative) occur, and if there is any reason that explains this fact.